Genetic diagnostic testing for PMP22 gene in Southwest Finland in 2005 – 2020. An observational, register-based study - Pankakoski, Pii (My University, 2025)
Variants of PMP22 gene are associated with neuropathic disorders: duplications of PMP22 with Charcot-Marie-Tooth disease type 1A (CMT1A), deletions of PMP22 with the hereditary neuropathy with liability to pressure palsies (HNPP), and PMP22 point mutations that may cause both CMT and HNPP phenotypes. The prevalence of CMT1A associated with PMP22 has been estimated at 1:3800 to 1:12500. The prevalence of HNPP is less well known. Diagnostics for CMT disorders and HNPP are based on assessment of the clinical presentation, family history, electrophysiological evaluation, and genetic testing. Multiplex ligation-dependent probe amplification is utilized for PMP22 copy number analysis since deletion and duplication variants are not detected by typical next generation sequencing panels or exome sequencing. In this study, the use, and findings of PMP22 gene analyses that were carried out in 2005–2020 at Turku University Hospital (TUH; Turku, Finland) were investigated. The purpose of the study was to determine the clinical characteristics of the investigated individuals, to evaluate the rate of diagnostic findings in the genetic tests, and to estimate the rate and spectrum of new genetic diagnoses of PMP22 associated neuropathies during this period. A total of 66 diagnostic findings were identified out of 244 tests. Highest diagnostic yield (45 %) was observed in patients in whom both clinical presentation and family history were suggestive of a genetic neuropathy. We found an incidence of 1.0:100 000 for PMP22 related neuropathies, 0.4:100 000 for PMP22 duplication, and 0.6:100 000 for PMP22 deletion. In this study, a significant part (57 %) of the genetic diagnoses were PMP22 deletions with a diagnostic rate of 33 %. We suggest that HNPP merits more research attention.
Keywords: neurology, genetic testing, pmp22, cmt, hnpp, hereditary neuropathy